2022
DOI: 10.1101/2022.11.18.517023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary metabolites produced byColletotrichumspp. on different olive cultivars

Abstract: This study was aimed to characterize the secondary metabolites produced by four Colletotrichum species, C. acutatum, C. gloeosporioides, C. godetiae and C. karsti, both in vitro, on potato dextrose agar (PDA) and oatmeal agar (OA), and during the infection process of fruits of four olive cultivars differing in susceptibility to anthracnose, Coratina and Ottobratica, both susceptible, Frantoio and Leccino, both resistant. The metabolites were extracted from axenic cultures after seven days incubation and from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As for Colletotrichum metabolites identified in this study, Colletofragarone A1, Colletoic acid and Pyrenocine A were reported to have phytotoxic and, in a few cases, cytotoxic properties [138,139]. Other compounds such as 5,4-dihydroxy-3,7,8-trimethoxy-6C-methylflavone and Apigenin-8-C-β-D-glucopyranoside, which in this study were found with a high relative abundance in all types of orange fruits examined, are reported in the literature as bioactive metabolites [101,103].…”
Section: Discussionmentioning
confidence: 67%
“…As for Colletotrichum metabolites identified in this study, Colletofragarone A1, Colletoic acid and Pyrenocine A were reported to have phytotoxic and, in a few cases, cytotoxic properties [138,139]. Other compounds such as 5,4-dihydroxy-3,7,8-trimethoxy-6C-methylflavone and Apigenin-8-C-β-D-glucopyranoside, which in this study were found with a high relative abundance in all types of orange fruits examined, are reported in the literature as bioactive metabolites [101,103].…”
Section: Discussionmentioning
confidence: 67%